2022
DOI: 10.1111/jgs.18155
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diagnosed (vs undiagnosed) dementia on family caregiving experiences

Abstract: Background Most older adults with Alzheimer's disease and related dementias (ADRD) do not receive a timely formal diagnosis, although formal diagnosis is linked to improved outcomes. Little is known about how a recognized formal diagnosis impacts family caregivers, who provide crucial support for older adults experiencing ADRD. Methods We analyzed 2017 National Health and Aging Trends Study and linked National Study of Caregiving data for a nationally representative sample of 724 (weighted n = 5,431,551) careg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…35 Improving caregiver communication activation may also improve caregiver self-efficacy and the caregiver's ability to advocate for the care recipient. 36,37 Self-efficacy is indicative of the dementia caregiver's confidence in managing care, obtaining community-based support, and acquiring medical information. 38 When caregivers of people with cognitive impairment learn that their role includes active communication with healthcare providers, medical visits are more patient- centered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Improving caregiver communication activation may also improve caregiver self-efficacy and the caregiver's ability to advocate for the care recipient. 36,37 Self-efficacy is indicative of the dementia caregiver's confidence in managing care, obtaining community-based support, and acquiring medical information. 38 When caregivers of people with cognitive impairment learn that their role includes active communication with healthcare providers, medical visits are more patient- centered.…”
Section: Discussionmentioning
confidence: 99%
“…15 Given that provider-led support is the most common source of information support for dementia caregivers, improving the quality of communication and collaboration with the healthcare team may facilitate greater access to information. 36 Dementia caregivers often have no understanding of the dementia prognosis and few recognize that dementia is a terminal disease that could benefit from palliative care. 44 Overall caregivers lack understanding about dementia disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Stress of Care Transitions Caregivers who helped someone with a formal diagnosis of dementia indicated more emotional difficulty and family disagreement than caregivers of individuals without a formal diagnosis. However, those caregivers of individuals with a formal dementia diagnosis were also more engaged in communication during doctors’ visits and also more likely to receive caregiver training than those who assisted someone without a diagnosis of dementia, suggesting the importance of linking support to dementia diagnostic procedures 544 Admitting a relative to a residential care facility has mixed effects on the emotional and psychological well‐being of dementia family caregivers.…”
Section: Caregivingmentioning
confidence: 99%
“…However, those caregivers of individuals with a formal dementia diagnosis were also more engaged in communication during doctors’ visits and also more likely to receive caregiver training than those who assisted someone without a diagnosis of dementia, suggesting the importance of linking support to dementia diagnostic procedures. 544 Admitting a relative to a residential care facility has mixed effects on the emotional and psychological well‐being of dementia family caregivers. Some studies suggest that distress remains unchanged or even increases for some caregivers (such as spouses), but other studies have found that distress decreases.…”
Section: Caregivingmentioning
confidence: 99%
See 1 more Smart Citation